Pengembangan Media Pembelajaran berupa Video Tutorial Materi Sulaman Burci - Suliyanthini, Dewi; Latifatuzzahroh, Latifatuzzahroh; Noerharyono, M. (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
This study aims to develop media video tutorials on burci embroidery materials to improve learning outcomes and student learning effectiveness. The method used in this study is the R&D method with the PPE (Planing, Production, Evaluation) model. The object of this research is a burci embroidery tutorial video development product. The subjects of this study were students of class XI Fashion Design at SMK Negeri 3 Cikarang Barat, with students XI A Fashion Design as a small group trial of 12 students, and students XI B Fashion Design as a large group trial of 38 students. The results of this study indicate that tutorial videos on burci embroidery material can improve learning outcomes and student learning effectiveness. The burci embroidery tutorial video obtained very decent criteria with a score of 95% for assessment by material experts and 83.3% for media experts. The burci embroidery tutorial video has proven to be effective in learning with the average score of students in the small group trials for the pre-test and for the post-test increasing to 85.17. The average score in the large group trials for the pre-test was 75.71 and for the post-test it increased to 85.13 with an average increase of 9.42. Overall, it can be concluded that the burci embroidery tutorial video media has proven to be very appropriate and effective to be used as a teaching aid in the subject of making fashion ornaments.